2014
DOI: 10.1590/1807-3107bor-2014.vol28.0056
|View full text |Cite
|
Sign up to set email alerts
|

Risk of leukemia in first degree relatives of patients with nonsyndromic cleft lip and palate

Abstract: The aim of this study was to determine the frequency of leukemia in parents of patients with nonsyndromic cleft lip and/or cleft palate (NSCL/P). This case-control study evaluated first-degree family members of 358 patients with NSCL/P and 1,432 subjects without craniofacial alterations or syndromes. Statistical analysis was carried out using Fisher's test. From the 358 subjects with NSCL/P, 3 first-degree parents had history of leukemia, while 2 out of 1,432 subjects from the unaffected group had a family his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…Several of the NSCL/P effects may extend into adulthood like an increased risk of cancer [17][18][19] . Previous studies have also shown a high risk of cancer in relatives of patients with NSCL/P 18,20 . This association has been explained, because cancer and NSCL/P may share similar genetic defects, which may be segregated within family 21,22 .…”
Section: Introductionmentioning
confidence: 89%
“…Several of the NSCL/P effects may extend into adulthood like an increased risk of cancer [17][18][19] . Previous studies have also shown a high risk of cancer in relatives of patients with NSCL/P 18,20 . This association has been explained, because cancer and NSCL/P may share similar genetic defects, which may be segregated within family 21,22 .…”
Section: Introductionmentioning
confidence: 89%
“…Epidemiological studies have shown a high risk of oral clefts in families with cancer, while others have provided consistent data about increased risk of cancer in patients with oral cleft and their relatives [1418]. This association has been explicated because specific cancers, including those of breast and stomach, and NSCL ± P may share similar genetic etiology [14, 1921].…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple candidate genes and genetic loci conferring susceptibility to NSOC have been associated with cancer risk [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], the genetic pathways underlying cancer and birth defects remain to be identified. Interestingly, NSOC is ultimately caused by interferences in cell proliferation, differentiation, survival, adhesion and migration, all of which are known to be involved in cancer [4].…”
Section: Discussionmentioning
confidence: 99%
“…The concept is that genes acting during the normal development may also have an important role in malignancies [6]. Over the past years, epidemiological studies have investigated the association of cancer with NSOC in different populations, including those from the United States, Southeast Asia, Denmark, Latvia, India, the Netherlands, Turkey, France, Poland, Pakistan, and Brazil [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], and the results are controversial. Thus, the aim of this study was to determine the frequency of NSOC in families of patients with a diagnosis of ALL.…”
Section: Introductionmentioning
confidence: 99%